EVIDENCE-BASED DENTISTRY: A CRITICAL ASSESSMENT OF CURRENT RESEARCH TRENDS AND THEIR INTEGRATION INTO CLINICAL DECISION- MAKING. - Najd Mohammed Abdullah Alrasheed, Norah Mansour Mohammed Albulayhi, Malikah Mohammed Ali Alqarni, Ayidh Ali Mohammed Alzamanan, Shaden Saleh Mohammed Saleh Aldrees (Chelonian Research Foundation, 2023)
Evidence-based dentistry (EBD) has become the establishment of aesthetic dentistry, emphasizing coordination as the most excellent proof with doctors and specialists. This article surveys current inquiries about EBD and investigates their effect on treatment choices. An efficient survey analyzes existing inquiries' ideas, findings, and impediments. We will talk about future investigation themes and techniques for coordination quality affirmation into dental hone. The article highlights the significance of EBD in improving understanding of care results and calls for endeavors to advance its utilization within the dental industry. Keywords: Evidence-based dentistry, clinical decision-making, research trends, integration, patient care outcomes